(untitled) (Journal of University of Babylon for Engineering Sciences, 2018)
The fifth generation technology or in short (5G technology) is the recent technology that is meant to break the data limits barrier. It promises very high data rates that will provide the user with enough bandwidth to conduct a real time HD telephone conversation. It will also provide the infrastructure for the IoT (Internet of Things) that will be dedicated for electronic governments, electronic healthcare centers, social media networks, full-scale data sharing, and remote controlling for sensitive governmental facilities. This paper is intended as survey for the current developments and technologies available for the coming 5G mobile technology. It discusses the ideas, the preparations, the developments, the standards under discussion and the potentials for this technology. In addition, this work takes into consideration the challenges and the difficulties facing this new coming technology and the plans laid ahead for the futuristic mobile networks.